2014
DOI: 10.1080/00063657.2014.988119
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and biomechanics of the nests of the Common BlackbirdTurdus merula

Abstract: Capsule Common blackbirds select different materials, with varying biomechanical properties, to construct different parts of their nest. Aims This study tested the hypothesis that outer components of a nest have a more structural role and so are stronger than materials used to line the cup. Methods Blackbird nests were measured prior to being dismantled to isolate structural components which were tested for mechanical strength and rigidity. Results Outer nest wall materials were significantly thicker, stronger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(100 citation statements)
references
References 25 publications
7
91
1
Order By: Relevance
“…Common House Martins Delichon urbicum have been shown to enhance the mechanical behaviour of mudbased nesting materials, particularly in compression, with the addition of polysaccharide/sugars obtained from abundant plant fruits (Silva et al 2010). In the nests of Common Blackbirds Turdus merula plant-derived materials in the outer nest were found to be thicker, stronger and more rigid compared to the materials present within the structural wall and the cup lining (Biddle et al 2015). A similar pattern was observed in the mechanical properties of materials used in the various parts of the nests of Eurasian Bullfinch Pyrrhula pyrrhula (hereafter 'Bullfinch') (Biddle et al 2017).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Common House Martins Delichon urbicum have been shown to enhance the mechanical behaviour of mudbased nesting materials, particularly in compression, with the addition of polysaccharide/sugars obtained from abundant plant fruits (Silva et al 2010). In the nests of Common Blackbirds Turdus merula plant-derived materials in the outer nest were found to be thicker, stronger and more rigid compared to the materials present within the structural wall and the cup lining (Biddle et al 2015). A similar pattern was observed in the mechanical properties of materials used in the various parts of the nests of Eurasian Bullfinch Pyrrhula pyrrhula (hereafter 'Bullfinch') (Biddle et al 2017).…”
Section: Introductionsupporting
confidence: 53%
“…Studies of the structural properties of nest materials are rare (Silva et al 2010;Biddle et al 2015Biddle et al , 2017Bailey et al 2016), so little is known about whether birds are generally selective of nest materials based on their biomechanical properties. It is also not known whether the species studied to date are representative of other species of similar size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeming and Biddle (2015) showed that vacuum-packing nests to remove air trapped within the walls significantly reduced the insulatory values of the nests but by only about 20% on average for four different species. Biddle et al (2015) showed that air gaps may be an important part of Bullfinch nests because they may allow convection currents through the walls. In Robin nests the presence of leaves may have trapped air, which acted in part as nest insulation but whether this idea is correct requires further investigation.…”
Section: Robins Nest In Enclosed Areas or Within Open-fronted Nestboxmentioning
confidence: 99%
“…This interest has considered the various roles of nests (Moreno, 2012;Mainwaring et al, 2014a;Deeming and Mainwaring 2015) as well as quantitative analysis of materials used in construction, which can be used to distinguish nests between species (Britt and Deeming, 2011;Crossman et al, 2011;Biddle et al, 2015Biddle et al, , 2016. Moreover, there are significant relationships between environmental conditions and nest composition with individuals of species nesting in colder, high latitude environments building better insulated nests (Crossman et al, 2011;Britt and This study investigated the materials used in nests of the European Robin (Erithacus rubecula) with particular reference to their role in determining the insulation afforded by the wall structure.…”
Section: Introductionmentioning
confidence: 99%